Peran UMKM Dalam Meningkatkan Keuangan Di Indonesia - Chavin A Hutauruk; emi emilestari; Dona Krisela Gultom (Publikasi Inspirasi Indonesia, 2025)
Abstract MSMEs in Indonesia face challenges of unstandardized financial management and low adoption of digital finance, despite stable daily transactions across regions. This research aims to analyze factors influencing MSMEs’ contribution to the formal financial system and formulate strategies to optimize financial literacy and IMC as solutions for digital payment adoption among low-budget MSMEs. The research uses a descriptive qualitative case study method on MSMEs in the culinary and retail sectors in several cities in Indonesia (7–16 October 2025), with primary data collected through observation and unstructured interviews, and secondary data from scientific publications and national MSME statistics. The results show that financial knowledge improves capital efficiency and access to financing, while social media and IMC accelerate digital payment adoption and transaction transparency. MSMEs play a crucial role as the main contributor to national GDP, the largest absorber of labor, and a significant foreign exchange potential in the creative digital and culinary sectors. The research concludes that literacy and capital limitations can be addressed through human resource development, expansion of KUR (People's Business Credit), and social media-based IMC. The implication emphasizes the need for synergy between digital financial inclusion policies, academic assistance, and IMC strategies as an adaptive financial model for low-cost micro-MSMEs to support sustainable real sector economic stability.